Policy Concept of Batam City Government in Tackling Illegal Billboards from the Perspective of Legal Effectiveness - Insti, Putri Deviana; Amboro, F. Yudhi Priyo; Sudirman, Lu (Universitas Medan Area, 2024)
Illegal billboards, which refer to billboards installed without a permit or in violation of applicable regulations, have become a pressing issue in many cities and regions. Its existence can harm the public by disturbing the aesthetics of the urban environment, disrupting traffic safety, and even damaging the natural environment. This research will examine the effectiveness of the Batam City government's policy in overcoming unauthorized advertisements, by considering the perspective of legal effectiveness theory which refers to five main aspects that must be considered, namely in terms of legal factors, law enforcement factors, legal facilities and infrastructure factors, community factors, and cultural factors themselves. This research also uses public policy theory. The method in this research uses empirical research methods with a qualitative approach. The results of this study show that the legal effectiveness of the concept of Batam city government policy against illegal billboards has not been effective, Batam city government policy still has several obstacles including less than optimal sanctions and in terms of law enforcement, there are still many people who are not concerned with the environment. Regarding the solutions applied by the Batam City government in eradicating illegal advertising using the need to make heavier sanctions than just demolition confiscation, for future concepts, the Batam City government plans to realize a new policy concept regarding billboard licensing regulations using an information technology system in the form of a Barcode on each billboard as an effort to tackle illegal billboards in the city of Batam.